Increased amounts of von Willebrand factor are bound to microparticles after infusion of desmopressin. (11th October 2012) - Trummer, A.; Haarmeijer, B.; Werwitzke, S.; Wermes, C.; Ganser, A.; Budde, U.; Tiede, A.
Summary Effects of desmopressin (DDAVP) in platelet disorders and primary haemostasis cannot be attributed solely to the increase in FVIII/VWF (von Willebrand factor), as VWF/FVIII concentrates have no effect in these circumstances. Microparticles (MP) can support haemostasis by expression of phospholipids, tissue factor and VWF on their surface. We hypothesized that significant amounts of VWF are bound to MP after DDAVP administration and that consequently depletion of MP should influence VWF:Ag and VWF:RCo plasma levels. Platelet‐poor plasma was either obtained well from healthy controls or before and after DDAVP administration from patients with von Willebrand's disease (type 1 or possible type 1) or patients with other bleeding disorders as controls. Concentrations of MP and VWF parameters were determined before and after MP depletion by different methods (magnetic bead selection, plasma microfiltration, ultracentrifugation). Platelet MP and VWF‐bearing MP were significantly increased after DDAVP. MP depletion by magnetic bead selection led to a significant reduction in VWF:Ag (−18.0%) and VWF:RCo (−27.7%) plasma levels without changes in VWF multimer composition. As results were similar for DDAVP control subjects, the amount of VWF bound to circulating microparticles was significantly higher after DDAVP administration compared with healthy controls (reduction −11.7%). DDAVP leads to a release of microparticles and increases the amount of VWF bound to microparticles which might explain the clinical efficacy of DDAVP in platelet disorders.